Analysis of regulation changes in judo - Bocioaca, L. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2018)
During its evolution, judo has undergone numerous regulation changes determined by the need to increase the spectacular character of the show and boost the fight. The research hypothesis consists in analysing these changes to see whether they produce effects on the preparation and participation in the competitions of the new Olympic cycle, and what measures and methods are necessary in the training of athletes. The purpose of this paper is to determine the effects produced by the main regulation changes on training and competition in top performance judo. Establishing and analysing these effects enable to schedule, plan and model preparation for the new Olympic cycle and achieve the intended results. The subjects are elite judo athletes aged 18 to 27 years, participants in the latest edition of the Olympics. Among the methods used to conduct the research, we mention: comparative data analysis, statistical processing, graphical representation. Statistical processing and comparative data analysis reveal the changes occurred in the training components. The increasingly dynamic and spectacular character of the competition, imposed by the media, requires modelling the physical, technical, tactical and psychological training. Thus, changing the technical rules generates effects on the physical preparation and exercise capacity, while changing the length and structure of the fight leads to modifications in the techniques and tactics of approaching the competition. Conclusions highlight the need to optimize preparation for all Olympic teams as regards the new effects of these changes on training and competition, determined by the periodic modification of the rules.